The Impact of Distance Education on Achieving the Effectiveness of the Educational Process During the Corona Pandemic, A Case Study on Princess Nourah University in Riyadh - Al-Kahtani, Sarah Homoud (Journal of Educational and Psychological Sciences, 2023)
The study aimed to find out the impact of using distance education on the success of the educational process in the Kingdom of Saudi Arabia during the Corona pandemic, which may help students to continue their education under various circumstances and crises. In addition, this study measured the effectiveness of distance education during the pandemic from the point of view of Princess Nourah University students in Riyadh. In order to achieve the objectives of the study, the researcher conducted opinion polls by distributing questionnaires to members of the target sample of Princess Nourah University students in Riyadh. Then, she analyzed the data to reach clear results. The study tool in its final form consisted of (34) phrases distributed on four axes, which measure the benefit from using distance education and its impact on the effectiveness of education at Princess Nourah University as a case study. The study reached several recommendations, including the need to pay attention to training and guidance programs. It also recommended focusing on programs that enable students to use distance education tools very well. They should provide easy and flexible communication channels between students and their teachers. The researcher also recommended that the authority which is responsible for digital and technological systems to develop the telecommunications network by improving and upgrading the level of Internet connectivity in all regions. The researcher also recommended more efforts by the Officials in the Ministry of Education to develop curriculum in line with the shift towards distance education.
Keywords: Distance education; educational effectiveness; Corona pandemic; Princess Nourah University